2023
DOI: 10.1155/2023/3333563
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Diabetic Neuropathic Pain and Downregulates p‐PKC and TRPV1 in Dorsal Root Ganglions and Spinal Cord Dorsal Horn

Abstract: Diabetic neuropathic pain (DNP) is a common complication of diabetes. Streptozotocin (STZ)-induced changes of protein in dorsal root ganglion (DRG) and spinal cord dorsal horn (SCDH) are critical for DNP genesis. However, which proteins change remains elusive. Here, the DNP model was established by a single intraperitoneal injection of STZ, accompanied by increased fasting blood glucose (FBG), decreased body weight (BW), and decreased paw withdrawal latency (PWL). Proteins change in L4-L6 DRGs and SCDH of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…Although there was slight reduction on day 21, the expression of p65 remained at a high level in comparison to control. Moreover, substance P and CGRP expression level in SCDH gradually enhanced from day 7 to day 21 and were higher than controls, which was similar with previous researches [33,34,37]. The elevated expression of p65, CGRP, and substance P may be one of the potential mechanisms contributing to the allodynia in DNP rats.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although there was slight reduction on day 21, the expression of p65 remained at a high level in comparison to control. Moreover, substance P and CGRP expression level in SCDH gradually enhanced from day 7 to day 21 and were higher than controls, which was similar with previous researches [33,34,37]. The elevated expression of p65, CGRP, and substance P may be one of the potential mechanisms contributing to the allodynia in DNP rats.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the possible upstream and downstream pathway inducing the increased expression of p65, substance P, and CGRP in SCDH of DNP rats still need further researches to explore. Previous study has showed electroacupuncture could inhibit the activation of p65 and substance P and CGRP expression in neuropathic pain-affected rats’ SCDH [37,38] and our research attempts to verify these results. The study demonstrated that the p65, substance P, and CGRP expression of DNP rats was all impaired after receiving the electroacupuncture treatment, even the expression level of p65 was lower than controls, indicating our result was same with previous studies [37,38].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Mice assigned to the EA group were treated with 2/100 Hz EA at the bilateral Yanglingquan (GB34) acupoints located between the heads of the tibia and fibula ( Figure 1 A) for 15 min daily from day 7 to day 14 after TNI or sham surgery. This treatment period has been shown to induce a stable antinociceptive effect on neuropathic pain [ 27 , 28 , 29 ]. Constant current square-wave electrical stimulation generated by a HANS acupoint nerve stimulator (HANS-200A, Nanjing Jisheng Medical Technology Co., Ltd., Nanjing, China) was administered via two acupuncture needles.…”
Section: Methodsmentioning
confidence: 99%